Non-Formal Education Model in Building Student Character in Mataram West Nusa Tenggara Indonesia - I Nyoman Wijana; Ni Putu Listiawati; Ni Luh Drajati Ekaningtyas (Green Publisher Indonesia, 2022)
This study aims to explore, analyze, and describe the non-formal pasraman education model in building the character of students in Mataram City, West Nusa Tenggara Indonesia. The research was conducted in non-formal Pasramans in Mataram City, using a qualitative method. The results of this study indicate that, non-formal pasraman as an educational institution has a role; (1) as a forum for deepening religious education, especially Hindu religious practices, in order to shape the habits and character of students, (2) to prepare and foster achievements in the Hindu religious field, as the basis for building self-confidence, (3) to shape and foster character religious students, (4) fostering a sense of brotherhood and communication between students, with the implementation of the teachings of Tri Hita Karana, as the basis for building the character of tolerance, cleanliness, and discipline, (5) as a medium for moral and ethical formation, in building the character of decency. Based on qualitative data analysis, it shows that the urgency of non-formal pasraman education is so important to shape the character of students, for that it is recommended that pasraman managers continuously improve the quality of learning, and in their management they should use professional management.